PENDAMPINGAN PROGRAM MEMBACA AL-QUR'AN USIA DEWASA DENGAN PETA KONSEP DAN KOSA KATA INDONESIA DI MAJELIS TA'LIM AHLUDZ DZIKRI SIDOARJO - Muhammad Alfi Syahrin; Heri Rifhan Halili; Ahmad Fuad Abdul Baqi; Adiba Maulidiyah; Moch. Salman Alfarizi (LPPM STAI Muhammadiyah Probolinggo, 2025)
This community service article describes a Qur'anic reading mentoring program for adult learners at Majelis Ta'lim Ahludz Dzikri Sidoarjo. The program was designed to respond to adults' difficulties in recognizing hijaiyah letters, connecting Arabic sounds with Indonesian explanations, and applying basic tajwid rules during recitation. The mentoring used concept maps and Indonesian vocabulary as learning aids so that participants could visualize the relationship among letters, vowels, articulation points, short-long sounds, and selected tajwid concepts. The program employed Participatory Action Research through planning, action, observation, reflection, and follow-up cycles. Thirty adult participants joined the mentoring once a week every Sunday from 10.00 to 11.30 WIB. Data were collected through initial reading diagnosis, observation notes, weekly practice records, oral reading assessment, and reflective dialogue with participants. The results indicate that concept maps helped participants organize Qur'anic reading materials into simpler and more memorable structures, while Indonesian vocabulary reduced anxiety and supported adult learners who had limited Arabic background. Participants became more confident in distinguishing similar letters, reading connected syllables, recognizing basic signs of vowels and sukun, and applying simple tajwid rules in short surahs. The main obstacles were limited practice time at home, different starting abilities, and hesitation among older participants. The mentoring shows that adult Qur'anic literacy can be strengthened through participatory, visual, and contextual learning strategies that respect learners' experiences and learning pace.